The end of reckoning – archival silences in the Germaine Greer Archive - Glanville , Lachlan (Archives & Manuscripts, 2017)
The Germaine Greer Archive was created by Greer in the 1970s to document her career and provide-counter evidence against false claims about her work and personal life. Later attempts to address gaps in the archive in relation to her television career were hampered by the poor record keeping of production companies and film and television archives. The archive documents both an attempt to create a complete record and the deliberate creation of a counter-narrative through arrangement and juxtaposition of records.